THE FORMATION OF DEMONOLOGICAL AND ANGELOLOGICAL IMAGES IN ENGLISH AND UZBEK CLASSICAL LITERATURE - Kuchiboyev Mansur Abdumurotovich (International Scientific and Current Research Conferences, 2026)
This article presents a comparative analysis of demonological and angelological images in English and Uzbek classical literature. The study examines the representations of angels and demons in the works of Geoffrey Chaucer, William Shakespeare, John Milton, as well as Nosiriddin Rabguzi, Alisher Navoi, Zahiriddin Muhammad Babur, and Abdurahmon Jami, highlighting the opposition between good and evil, the divine and the diabolical. It also explores the influence of Christian and Islamic theological-philosophical traditions, Sufi thought, and mythological consciousness on the formation of these images. The paper identifies common and distinctive features of Eastern and Western literary thinking and reveals their artistic and philosophical significance.